The Role of Guidance and Counselling in Enhancing Academic Achievement in Secondary Schools - Qamar Zaman Bhutto *; Jam Muhammad Zafar; NaeemUllah (Al-Qanṭara, 2023)
This article focuses on the importance of guidance and counselling services for improving learning outcomes provided to secondary school students in the Larkana Division. The primary objective of practical guidance and counselling is to support students in aligning their strengths, enhancing their learning outcomes, nurturing their interests and values, and ultimately facilitating the realisation of their complete potential. The primary objective of this effort is to enhance the academic outcomes of students in a given school. Hence, it is recommended in the document that the establishment of additional guidance and counselling centres staffed with a more significant number of qualified counsellors be provided in secondary schools. Furthermore, it is suggested that the government extend practical assistance to guidance and counselling initiatives by allocating financial resources. The primary objective of this article was to study the impact of guidance and counselling service for improving learning outcomes of students. Moreover, the study suggests that it is imperative to provide comprehensive and enlightening training to all teachers in secondary schools regarding the significance of providing complete support to guidance and counselling programmes inside their educational institutions. Furthermore, it is imperative to address the prevailing unfavourable perception of guidance and counselling among many students and parents. Moreover, this paper aims to provide a comprehensive understanding of the concept of guidance and counselling, various types of guidance and counselling, the significance of guidance and counselling in enhancing students' learning outcomes. The objectives of guidance and counselling in educational institutions, and the challenges encountered in implementing guidance and counselling programmes in schools, will be studied among other related topics. The present discourse emphasises the domains of guidance and counselling, with a particular focus on the aspects of effectiveness and learning. Lastly, due to the inherent nature of the study, an analytical approach is employed during the research process.